The Impact Of Brand Experiences On Brand Loyalty: Mediating Role Of Brand Love In Fore Coffee - Rasyid Zaky Rachman Hakim; Nurliya Apriyana (SEAN Institute, 2024)
This study aims to examine the effect of brand experience on brand loyalty with brand love as a mediating variable, in the context of Fore Coffee consumers in Indonesia. The focus of this study is to understand the extent to which brand experience that includes sensory, intellectual, and behavioral aspects can influence customer loyalty through the formation of emotional bonds to the brand (brand love). By using quantitative descriptive methods and data collection through an online survey of 100 respondents, the results of the study indicate that brand experience has a significant positive effect on brand love and brand loyalty. However, mediation analysis shows that brand love does not significantly mediate the relationship between brand experience and brand loyalty. This finding confirms the importance of positive brand experience in increasing customer loyalty directly, without the need for full emotional involvement. This study provides practical implications for the development of Fore Coffee's marketing strategy and suggests the importance of brand experience innovation to build customer loyalty in the competitive coffee industry.